Analisis Faktor Yang Berhubungan Dengan Kejadian HIV/AIDS Pada Laki-Laki Di Wilayah Kerja Puskesmas Simpur Bandar Lampung Tahun 2023 - Fidel Rama Nugraha; Wayan Aryawati; Christin Angelina Febriani (PROFESSIONAL HEALTH JOURNAL, 2024)
Abstract HIV/AIDS is one of the top-ranking infectious diseases that can lead to death. One of the five nations with a sizable number of cases is Indonesia. Out of Indonesia's 250 million people, the LGBT community numbers about 7.5 million. With 248 instances recorded, data from the Bandar Lampung City Health Office on HIV/AIDS cases at the Simpur Community Health Center, broken down by gender, reveals that men are more likely to contract the disease than women. The goal of this study is to examine the risk variables connected to the development of HIV/AIDS in men within the Simpur Community Health Center's service area in Bandar Lampung in 2023. A case-control strategy is used in the quantitative research methodology. There are 180 men in the study population, making 153 guys in the sample. Purposive sampling is the method of choice for sampling, while univariate, bivariate (chi-square), and multivariate (logistic regression) studies are employed for data analysis. According to the findings of the univariate analysis, 66.7% of people do not have HIV/AIDS while 33.3% have. HIV/AIDS and occupation (p-value=0.003), knowledge (p-value=0.005), marital status (p-value=0.0001), and sexual history (p-value=0.017) all show positive correlations in the bivariate analysis. Traumatic experiences have the highest impact on the likelihood of developing HIV/AIDS (p-value < 0.0001) and an odds ratio (OR) of 38613. Families, close friends, and healthcare professionals are urged to offer ongoing support, care, education, and counseling to HIV/AIDS patients in order to keep them motivated and stop the spread of the disease Keywords: HIV, AIDS, Knowledge